The lived experiences of Black and Minority Ethnic patients within a high security hospital - Hui, Ada M.L. (Health Education England, 2017)
Black and minority ethnic (BME) communities are disproportionately overrepresented in mental health and legal systems within the UK. People from BME communities are detained more frequently, receive poorer mental health care, and are restrained and secluded more often than individuals from non-BME backgrounds. High security hospitals represent the physical spaces in which mental health and legal disciplines merge, thereby offering unique contexts for study.